2018
DOI: 10.20944/preprints201801.0225.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation of Fish Skin Gelatin-Based Nanofibers Incorporating Cinnamaldehyde by Solution Blow Spinning

Abstract: Cinnamaldehyde, a natural preservative that can non-specifically deactivate foodborne showed antibacterial activity by direct diffusion and vapor release against Escherichia coli O157:H7, 26Salmonella typhimurium, and Listeria monocytogenes. Inhibition zones increased as cinnamaldehyde 27 ratio increased. Nanofibers showed larger inhibition effects than films prepared by casting method 28 when S. typhimurium was exposed to the released cinnamaldehyde vapor, although films had higher 29 remaining cinnamaldehyd… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…30 In the study of Liu et al, antibacterial fish skin gelatin-based NF incorporating cinnamaldehyde was fabricated to be used in controlled-release applications. 31 In another study, electrospun chitosan/poly-(ethylene oxide) mats including cinnamaldehyde having antibacterial activity against pseudomonas bacteria was engineered in order to be potentially used for alleviating nosocomial infections. 32 In a very recent study, electrospun fibrous film was developed to be used in food industry from the pea protein isolate-polyvinyl alcohol with cinnamaldehyde cooperation to obtain a material showing antibacterial activity against both Gram-positive and -negative bacteria.…”
Section: ■ Introductionmentioning
confidence: 99%
“…30 In the study of Liu et al, antibacterial fish skin gelatin-based NF incorporating cinnamaldehyde was fabricated to be used in controlled-release applications. 31 In another study, electrospun chitosan/poly-(ethylene oxide) mats including cinnamaldehyde having antibacterial activity against pseudomonas bacteria was engineered in order to be potentially used for alleviating nosocomial infections. 32 In a very recent study, electrospun fibrous film was developed to be used in food industry from the pea protein isolate-polyvinyl alcohol with cinnamaldehyde cooperation to obtain a material showing antibacterial activity against both Gram-positive and -negative bacteria.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Analysis of the viscoelastic properties of RSF formulations is of interest since solution viscosity determines whether a droplet spray or continuous fibers are obtained, as it affects initial droplet shape and stability of the jet trajectory during SBS. 47 The viscosity measurements of RSF formulations of formic acid and the aqueous system at increasing concentrations are shown in Figure 1a,b. Both systems exhibited slightly different rheologies over the range of concentrations tested.…”
Section: Resultsmentioning
confidence: 99%
“…2015; Liu et al . 2018b). Previous reports have shown that the viscosity of the polymeric solution increases as a result of the incorporation of the constituents of the essential oil, and the fibre diameter is affected (Liu et al .…”
Section: Characterization Of Nanofibresmentioning
confidence: 99%
“…Mori et al (2015) showed that the addition of essential oil from candeia to the polymeric solution resulted in an increase in the average diameter of the nanofibres obtained; this fact corroborates the results obtained in this study. Studies suggest that the viscosity and surface tension of the solution are key parameters during the formation of the nanofibres, and the increase in the viscosity of the solutions is the result of the increase in the diameter of the nanofibres (Silva et al 2015;Liu et al 2018b). Previous reports have shown that the viscosity of the polymeric solution increases as a result of the incorporation of the constituents of the essential oil, and the fibre diameter is affected (Liu et al 2018a(Liu et al , 2018b, similarly to what was reported in this work.…”
Section: Characterization Of Nanofibresmentioning
confidence: 99%